Online Learning During the Covid-19 Pandemic: Preservice Teacherâ€™s Perception - Agus Muliadi; Saiful Prayogi; Farida Bahalwan; Wa Nirmala; Ni Nyoman Sri Putu Verawati (Jurnal Penelitian Pendidikan IPA, 2021)
This study aims to explore preservice teacherâ€™s perception of online learning during the Covid-19 pandemic. This study is a descriptive-exploratory research where respondents are 107 preservice teachers from four study programs that provide preservice teacherâ€™s education, namely Mathematics Education, Biology Education, Physics Education, and Chemistry Education in the Mandalika University of Educationâ€“Indonesia. An instrument in the form of a questionnaire was used with a Likert scale and has been validated (expert validation). The research data were analyzed descriptively and statistically using the analysis of variance (ANOVA) test. The study results show that the preservice teacherâ€™s perception of online learning modes during the Covid-19 pandemic is â€œquiteâ€ category, and there is no significant difference in preservice teachers' perceptions of online learning during the Covid-19 pandemic. Descriptions of the results of further studies are presented in this article